Buku Saku Digital Bermuatan IDEAL Problem Solving Berbasis Ethnomatematika Terhadap Kemampuan Pemecahan Masalah - Eka Putri Ayuningsih; Muhamad Firdaus; Yudi Darma (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2023)
Abstract. This study aims to produce learning media in the form of android applications that achieve valid, practical and effective criteria so that they are suitable for use. This research uses Research And Development (R&D) methodology. The steps for developing this application are using a 4D model but only done up to 3D which stands for define, design, develop. The subjects in this study were 19 students of class VII MTs AL Mustaqim. The instruments used in this study were media and material expert validation sheets, student and teacher response questionnaires, and a posttest.The research results related to the validity of reaching the level of validity with the category of